5+1 Newspaper Organizer: A Classroom Strategy for Developing Students’ Reading Skill - Nurlina Nurlina; Supiani Supiani; Iwan Perdana (Universitas Majalengka, 2021)
The objectives of this study are to investigate the implementation of the 5+1 Newspaper Organizer as a strategy in developing the students’ reading skills and to find out the students’ and teacher’s responses when the 5+1 newspaper organizer strategy is implemented at the teaching and learning activities. The qualitative method is employed in this study in which the data are collected from observation, interview, and documentation at a junior high school in South Kalimantan province, Indonesia. The findings report that the use of 5+1 newspaper organizer contributed positively to students’ reading skill because it helped them find main ideas, the meaning of words, and the explicit and implicit information of the text easily. They worked collaboratively by sharing ideas and learning texts together. They were also engaged with the strategy and felt happy, enthusiastic, and active at the reading class because the teacher gave the students with more opportunity to work in a group without feeling shy or doubt to learn it. Therefore, the 5+1 Newspaper Organizer is an effective strategy for developing students’ reading ability.